From nature reserve to mosaic management: Improving matrix survival, not permeability, benefits regional populations under habitat loss and fragmentation. Issue 6 (21st February 2022) - Yamaura, Yuichi; Fletcher, Robert J.; Lade, Steven J.; Higa, Motoki; Lindenmayer, David
Abstract: Although matrix improvement in fragmented landscapes is a promising conservation measure, matrix permeability (willingness of an organism to enter the matrix) and movement survival in the matrix are usually aggregated. Consequently, it is unknown which matrix property needs to be improved. It also remains unclear whether matrix upgrading from dispersal passage to providing reproduction opportunities has large conservation benefits and whether there are interactive effects between habitat and matrix management. We examined matrix effects on regional populations across a gradient of habitat loss and fragmentation using simulation experiments that integrated demographic processes and movement modelling based on circuit theory. We separately modified the levels of matrix permeability and movement survival to evaluate their individual effects. We also altered the amount and configuration of not only habitat but also improved matrix to assess their effects on population vital rates (size, survival and density). In binary landscapes comprising habitat and unimproved matrix, matrix movement survival had larger effects on population vital rates than matrix permeability. Increasing movement survival increased vital rates, yet, increasing matrix permeability decreased vital rates. Increased permeability required corresponding increased movement survival to offset potential negative population outcomes. When subsets of the matrix functioning as dispersal passage only (where no reproduction opportunities existed) were improved, increasing matrix permeability but holding movement survival constant reduced all vital rates, especially with increasing habitat fragmentation. In contrast, when movement survival increased, vital rates increased given strong habitat fragmentation. The benefits of upgrading dispersal passage to provide reproduction opportunities for population survival were greatest when habitat amount was moderate. We also found synergetic effects between amounts of habitat and improved matrix, and the benefits of matrix improvement were promoted when improvement was achieved in a spatially aggregated manner. Synthesis and applications . Matrix improvement and connectivity modelling aimed at increasing movement survival will likely bring larger conservation benefits than those for improving permeability alone. Buffering and connecting habitat remnants with improved matrix could provide benefits as long as movement survival is increased. Simultaneous implementation of habitat management and matrix improvement would yield synergistic conservation benefits. Abstract : Matrix improvement and connectivity modelling aimed at increasing movement survival will likely bring larger conservation benefits than those for improving permeability alone. Buffering and connecting habitat remnants with improved matrix could provide benefits as long as movement survival is increased. Simultaneous implementation of habitat management and matrix improvement would yield synergistic conservation benefits. 日本語要旨: 分断化景観でのマトリックスの改善は有望な保全手法だが、マトリックスの透過性（生物がマトリックスに入る確率）とマトリックスでの移動生存率は通常まとめて扱われ、いずれのマトリックスの属性を改善すべきか不明である。また、マトリックスを移動通路から繁殖の機会を提供するまで改善すると大きな保全上の便益が得られるのか、生息地とマトリックスの管理の間に交互作用があるのかも明らかになっていない。 私たちは、人口統計学的過程とサーキット理論に基づいた移動モデルを統合したシミュレーション実験を行ない、生息地の消失と分断化の傾度上で、地域個体群にマトリックスが及ぼす影響を調査した。ここで異なるマトリックスの属性としてマトリックスの透過性と移動生存率を個別に変化させ、個々の影響を評価した。また生息地だけでなく改善したマトリックスの量と配置も変化させ、個体群統計量（サイズ、生存、密度）に及ぼす影響を調査した。 生息地と改善されていないマトリックスからなる二値の景観では、マトリックスの移動生存率は透過性よりも個体群統計量に大きな影響を及ぼしていた。移動生存率の増加は個体群統計量を増加させたが、透過性の増加は個体群統計量を減少させた。透過性の増加が個体群に及ぼす潜在的な負の影響を相殺するためには、移動生存率の増加が必要とされた。 移動通路としてのみ機能するマトリックス（繁殖の機会は存在しない）の一部を改善する場合、移動生存率を一定にしてマトリックスの透過性を増加させるとすべての個体群統計量が特に生息地が分断化した場合に大きく減少した。対照的に、移動生存率が増加すると、個体群統計量は強度の生息地の分断化下で増加した。マトリックスを移動通路から繁殖の機会を提供するまで改善すると、生息地の量が中程度の際に個体群生存率への便益は最も大きかった。生息地と改善マトリックスの量の間には相乗効果があり、マトリックス改善は空間的にまとめて実施すると便益が大きくなった。 まとめと応用：マトリックスの改善と連結性のモデリングは移動生存率の増加を目指して行なうと、透過性のみを改善する場合に比べて保全上の便益が大きいだろう。改善マトリックスで残存生息地の緩衝帯を設け、残存生息地間を連結させることは、移動生存率が増加するならば便益を生むだろう。生息地の管理とマトリックスの改善を同時に実施すれば、相乗的な保全上の便益がもたらされるだろう。